Ethical Behaviour of Tertiary Education Students in Cyprus - Zopiatis, Anastasios; Krambia-Kapardis, Maria (My University, 2008)
The purpose of this research was to investigate, for the first time, tertiary education students’ ethical judgements in the Republic of Cyprus academic environment. The authors developed and administered a quantitative questionnaire to a sample of 1,000 individuals currently pursuing accredited degrees at two tertiary institutions. Statistical analysis revealed four factors, named violation of school regulations, selfishness, cheating, and computer ethics that describe students’ ethical judgements in the academic environment. The results indicate that students exhibit the lowest tolerance with ethical issues relevant with selfishness and highest with issues relevant with computer ethics. In addition, a number of differences were revealed when the authors investigated the relationship between the four retained factors and variables such as gender, year of study, type of academic discipline, and religion. Finally, reflecting on the research findings, a number of practical recommendations are made mainly to educational institutions that wish to redefine their policies and procedures regarding ethics within their academic environment.
Keywords: Cyprus; Tertiary education; Students ethical standing; Cyprus; Tertiary education; Students ethical standing